ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN DALAM MEMBELI PRODUK PEMBALUT WANITA SOFTEX HELLO KITTY - Bunga Bintang Maharani; Bulan Prabawani; Sari Listyorini (Universitas Diponegoro, 2015)
Softex Hello Kitty was entering the market with the target market teenagers, doing promotions such as advertisement and promotion programs with prizes. Product design and catchy packaging are the advantages of the product. Nevertheless, brand Softex are still behind competitors. Therefore, it is necessary to know what factors influence consumers to buy Softex Hello Kitty. The type of this research is exploratory research. The samples are 100 respondents using non probability sampling technique with purposive sampling approach. The analysis method is quantitative analysis, consist of exploratory factor analysis and regression test using SPSS 15.0 for windows. The research concluded factors that influence consumers to buy Softex Hello Kitty are price, product attribute, promotions, demography, and social. That factors have positive and significant effect to purchase decision. Suggestions can be submitted are product innovation that suitable with the consumers conditions, increase the promotion programs with gift and bonus, also more active to informing the product.